Development of recommendations on creating local formulary drug list for children affected with gastritis and duodenitis - V. V. Trokhymchuk; I. V. Vyshnytska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
An urgent task is to carry out regular quality control and rational prescribing of drugs, changes to the drug formulary lists for the purpose of positive influence on the processes of pharmaceutical provision, especially children affected with gastritis and duodenitis. The aim of the work was to create a list of the recommended groups of drugs for further development of the local insurance and formulary drug lists used for treatment of children with gastritis and duodenitis using modern information technologies. Methods of peer reviews, questionnaires, direct observation, modeling, and information analysis were used in the process. The objects of study were regulatory and legislative documents, medication treatments sheets, price lists of wholesale pharmaceutical companies, forms of expert assessments. Science-based guidelines for the assessment of the economic costs for the inclusion of medicines in local formulary drug lists of health care institutions to help children with gastritis and duodenitis in the acute stage, in specialized hospitals, taking into account peculiarities of the disease under study at the regional level were formed. According to the results of a comprehensive study of pharmaceutical provision for treatment of children with gastritis and duodenitis, in addition to an expert evaluation of medicines, recommendations for the creation of a local formulary drug list were made and recommended list of drug groups was determined by 15 INN drugs to be used in the development of a local drug formulary list for pharmacotherapy of the pathology under study.